Decolonial Museology, Space Travel and the Mineral Cabinet - Alana Osbourne (Museum & Society)
Taking the Africa Museum’s mineral cabinet as a point of departure, I probe the entanglements of inorganic matter, coloniality, and mining for space travel. Through museum ethnography, and by thinking about minerality as a field that connects intra and extra-terrestrial interests, my research unpacks how colonial logics permeate relationships between earthbound and outer spaces. From this vantage point, I investigate how the calls for decolonial practices that resonate within museums studies relate to futurities that are embroiled in imperial logics of space conquest and mining.